Problematic MPR Decree Post Reform and After The Issuance of Law No. 12 of 2011 - Sulardi Wijaya (Universitas Muhammadiyah Sidoarjo, 2015)
The existence of Tap. MPR Post 1945 Amandement to the issuance of Law No. 12 of 2011 has given an opportunity for the Assembly to create a new Tap. MPR outside from the valid one. At the time how judicial review of laws that conflict with the Tap. MPR, and how judicial review of the Tap. MPR are contrary to the Constitution is necessary to realize justice and balance. One of the powers of the Constitutional Court (MK) in paragraph C of Article 24 (1) Constitution of 1945 is hear at the first and the last with a final decision to the laws of Constitution. So if there are laws that conflict with the MPR or MPR and contrary to the Constitution, the authority to test the authority of the Constitutional Court instead. How To Cite: Wijaya, S. (2015). Problematic MPR Decree Post Reform and After The Issuance of Law No. 12 of 2011. Rechtsidee, 2(1), 53-64. doi:http://dx.doi.org/10.21070/jihr.v2i1.6